MRSA in persons not living or working on a farm in a livestock-dense area: prevalence and risk factors. (15th December 2016) - Zomer, Tizza P.; Wielders, Cornelia C. H.; Veenman, Christiaan; Hengeveld, Paul; van der Hoek, Wim; de Greeff, Sabine C.; Smit, Lidwien A. M.; Heederik, Dick J.; Yzermans, C. Joris; Bosch, Thijs; Maassen, Catharina B. M.; van Duijkeren, Engeline
Abstract : Objectives: MRSA emerged in livestock and persons in contact with livestock is referred to as livestock-associated MRSA (LA-MRSA). We assessed the prevalence and risk factors for MRSA carriage in persons not living or working on a farm. Methods: A cross-sectional study was performed among 2492 adults living in close proximity of livestock farms. Persons working and/or living on farms were excluded. Nasal swabs were cultured using selective media. Participants completed questionnaires and the distance from the residential address to the nearest farm was calculated. The Mann–Whitney U -test was used to compare median distances. Risk factors were explored with logistic regression. Results: Fourteen persons carried MRSA (0.56%; 95% CI 0.32%–0.92%), 10 of which carried LA-MRSA of multiple-locus variable-number tandem repeat analysis complex (MC) 398 (0.40%; 95% CI 0.20%–0.71%). MRSA MC 398 carriers lived significantly closer to the nearest farm than non-carriers (median: 184 versus 402 m; P  <   0.01). In bivariate analyses correcting for contact with livestock, this difference remained significant. Conclusions: Although the prevalence was low, living near farms increased the risk of MRSA MC 398 carriage for persons not living or working on a farm. Further research is necessary to identify the transmission routes.